2004
DOI: 10.1073/pnas.0308653100
|View full text |Cite
|
Sign up to set email alerts
|

Trends between gene content and genome size in prokaryotic species with larger genomes

Abstract: Although the evolution process and ecological benefits of symbiotic species with small genomes are well understood, these issues remain poorly elucidated for free-living species with large genomes. We have compared 115 completed prokaryotic genomes by using the Clusters of Orthologous Groups database to determine whether there are changes with genome size in the proportion of the genome attributable to particular cellular processes, because this may reflect both cellular and ecological strategies associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
355
5
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(407 citation statements)
references
References 31 publications
45
355
5
2
Order By: Relevance
“…10 and 11 show, our experiments with RAevol reproduce qualitatively the scaling laws observed in the prokaryotic kingdom (Cases et al, 2003;van Nimwegen, 2003;Konstantinidis and Tiedje, 2004;Molina and van Nimwegen, 2008). Small genomes with few genes only have a very basic regulation activity while large ones develop complex regulation networks with many genes.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…10 and 11 show, our experiments with RAevol reproduce qualitatively the scaling laws observed in the prokaryotic kingdom (Cases et al, 2003;van Nimwegen, 2003;Konstantinidis and Tiedje, 2004;Molina and van Nimwegen, 2008). Small genomes with few genes only have a very basic regulation activity while large ones develop complex regulation networks with many genes.…”
Section: Discussionsupporting
confidence: 48%
“…Through the analysis of the annotated sequences, it was shown that the number of genes in each functional category scales as a power-law of the total number of genes in the genome and that the exponent of this law depends on the functional role of the family: the number of transcription factors (TFs), in particular, scales quadratically with the total number of genes while metabolic genes scale at most linearly with it (van Nimwegen, 2003;Molina and van Nimwegen, 2008). Moreover, this increase is also correlated with the size of the genome (Konstantinidis and Tiedje, 2004). These results suggest that the intricacy of regulation networks grows faster than the size of the network itself.…”
Section: Introductionmentioning
confidence: 99%
“…On average, the genomes of soil prokaryotes are larger than those inhabiting aquatic ecosystems 27 or the human gut 28 . These relatively large genomes are thought to provide soil-dwelling bacteria with a more diverse genetic inventory to enhance survival in conditions where resources are diverse, but sparse 29,30 . However, the Ca.…”
Section: Resultsmentioning
confidence: 99%
“…In general, large genomes are thought to be more ecologically versatile (Konstantinidis and Tiedje, 2004), which would thus be important for an environmentally acquired symbiont that has both free-living and host-associated stages. The estimated genome sizes of the Osedax symbionts, larger than free-living relatives, and similar to the facultative intracellular endosymbiont Teredinibacter turnerae of the marine shipworm bivalve (Table 1; Yang et al, 2009), indirectly suggests a possible retention of genes for both free-living and intracellular existence.…”
Section: Evidence For a Free-living Lifestagementioning
confidence: 99%